A longitudinal study of burden among spouse and non-spouse caregivers of older adults with stroke-induced-dependency - Carolina Baltar Day; Carla Cristiane Becker Kottwitz Bierhals; Fernanda Laís Fengler Dal Pizzol; Gail Low; Naiana Oliveira dos Santos; Lisiane Manganelli Girardi Paskulin (Associação Brasileira de Enfermagem, 2023)
ABSTRACT Objective: to assess the burden of spouse and non-spouse caregivers of older adults with stroke-induced-dependency after discharge from a university hospital's Specialized Care Stroke Unit in southern Brazil. Methods: a longitudinal survey. The sample consisted of 48 consenting caregivers, among which 20 were spouse caregivers. Data were collected between May 2016 and July 2018. One week after discharge, caregivers completed a sociodemographic profile, the Functional Independence Measure, and the Caregiver Burden Scale. Burden was also measured two months after discharge. Data were analyzed using Multivariate Analyses of Variance. Results: regarding time 1, non-spouse caregivers experienced greater burden with respect to social isolation (p = .01). Along with a persistently greater sense of isolation (p=.04), non-spouse caregivers felt far greater general strain (p =.01). Conclusion: statistically significant differences in burden over time highlight the importance of assessing caregiver burden after discharge and the need for a formal support program.